2004
DOI: 10.1194/jlr.m300455-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Formation and antiproliferative effect of prostaglandin E3 from eicosapentaenoic acid in human lung cancer cells

Abstract: We investigated the formation and pharmacology of prostaglandin E 3 (PGE 3 ) derived from fish oil eicosapentaenoic acid (EPA) in human lung cancer A549 cells. Exposure of A549 cells to EPA resulted in the rapid formation and export of PGE 3. The extracellular ratio of PGE 3 to PGE 2 increased from 0.08 in control cells to 0.8 in cells exposed to EPA within 48 h. Incubation of EPA with cloned ovine or human recombinant cyclooxygenase 2 (COX-2) resulted in 13-and 18-fold greater formation of PGE 3 , respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
84
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 35 publications
(49 reference statements)
6
84
0
Order By: Relevance
“…EPA not only can replace arachidonic acid in phospholipid bilayers but is also a competitive inhibitor of COX, reducing the production of 2-series PGs and thromboxane, in addition to the 4-series leukotrienes (11,12). Recent studies have also shown that 3-and 5-series eicosanoids derived from EPA are either less biologically active or inactive compared with the former products and are thus considered to exert effects that are less inflammatory (10,13,39,40). Furthermore, Serhan (14,15,39,41,42) and co-workers have described a group of polyoxygenated DHA and EPA derivatives termed Resolvins that are produced enzymatically in various tissues.…”
Section: Discussionmentioning
confidence: 99%
“…EPA not only can replace arachidonic acid in phospholipid bilayers but is also a competitive inhibitor of COX, reducing the production of 2-series PGs and thromboxane, in addition to the 4-series leukotrienes (11,12). Recent studies have also shown that 3-and 5-series eicosanoids derived from EPA are either less biologically active or inactive compared with the former products and are thus considered to exert effects that are less inflammatory (10,13,39,40). Furthermore, Serhan (14,15,39,41,42) and co-workers have described a group of polyoxygenated DHA and EPA derivatives termed Resolvins that are produced enzymatically in various tissues.…”
Section: Discussionmentioning
confidence: 99%
“…EPA not only can replace arachidonic acid in phospholipid bilayers but is also a competitive inhibitor of cyclooxygenase, reducing the production of 2-series PGs and thromboxane, in addition to the 4-series leukotrienes. As noted, the 3-and 5-series eicosanoids (respec- tively) derived from EPA are either less biologically active or inactive as compared with the former products and are thus considered to exert effects that are less inflammatory (34,35). Further, Serhan and colleagues (14 -17) have described a group of polyoxygenated DHA and EPA derivatives termed resolvins that are produced in various tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Syntheses of PGE 2 and PGE 3 are catalyzed by the same COX, but the biological effects of PGE 2 and PGE 3 are distinct. PGE 2 has been shown to promote cancer development (5-7), whereas PGE 3 has been recently found to have anticancer effects (9). Until recently, PGE 3 was an underappreciated and poorly understood eicosanoid because of the lack of sensitive and convenient methods for its measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism of the n-6 AA (20:4n-6) and the n-3 EPA (20:5n-3) by the COX pathway produces PGs of two (e.g., PGE 2 ) and three series (e.g., PGE 3 ), respectively. These metabolites, PGE 2 and PGE 3 , have been shown to differently affect cancer growth (5)(6)(7)(8)(9). To determine the impact of the change in tissue ratio of n-6͞n-3 fatty acids as a result of fat-1 expression on the generation of the cancerrelated eicosanoids, we chose to measure the contents of PGE 2 and PGE 3 in melanoma and stromal tissues of fat-1 transgenic and WT mice by using lipid mediator lipidomics [liquid chromatography (LC)-UV-tandem MS (MS͞MS)].…”
Section: Differential Profiles Of Eicosanoids In B16 Melanoma and Strmentioning
confidence: 99%
See 1 more Smart Citation